Improvement in osteogenesis, vascularization, and corrosion resistance of titanium with silicon-nitride doped micro-arc oxidation coatings - Shen, Yiding; Fang, Kai; Xiang, Yun; Xu, Keyuan; Yu, Liang; Chen, Jiaquan; Ma, Pingping; Cai, Kaiyong; Shen, Xinkun; Liu, Jinsong (Frontiers in Bioengineering and Biotechnology, 2022)
Titanium (Ti) implants have been widely used for the treatment of tooth loss due to their excellent biocompatibility and mechanical properties. However, modifying the biological properties of these implants to increase osteointegration remains a research challenge. Additionally, the continuous release of various metal ions in the oral microenvironment due to fluid corrosion can also lead to implant failure. Therefore, simultaneously improving the bioactivity and corrosion resistance of Ti-based materials is an urgent need. In recent decades, micro-arc oxidation (MAO) has been proposed as a surface modification technology to form a surface protective oxide layer and improve the comprehensive properties of Ti. The present study doped nano silicon nitride (Si3N4) particles into the Ti surface by MAO treatment to improve its corrosion resistance and provide excellent osteoinduction by enhancing alkaline phosphatase activity and osteogenic-related gene expression. In addition, due to the presence of silicon, the Si3N4-doped materials showed excellent angiogenesis properties, including the promotion of cell migration and tubule formation, which play essential roles in early recovery after implantation.